(untitled) (Polish Yearbook of International Law, 2017)
This article discusses defnitions of crimes included into the Act of 18 December 1998 on the Institute of National Remembrance – Commission for the Prosecution of Crimes against the Polish Nation, and their usefulness in prosecuting individuals who committed internationa crimes. It is argued that the provisions of the Act cannot constitute a ground for criminal responsibility of individuals, as they violate the principle of nullum crimen sine lege certa.